Enhancing dendrobine production in Dendrobium nobile through mono-culturing of endophytic fungi, Trichoderma longibrachiatum (MD33) in a temporary immersion bioreactor system - Sarsaiya, Surendra; Jain, Archana; Shu, Fuxing; Yang, Mingfa; Pu, Mengxuan; Jia, Qi; Gong, Qihai; Wu, Qin; Qian, Xu; Shi, Jingshan; Chen, Jishuang (Frontiers in Plant Science, 2024)
Dendrobine, a valuable alkaloid found in Dendrobium nobile, possesses significant pharmaceutical potential. In this study, we explored innovative approaches to enhance dendrobine production by utilizing endophytic fungi in a Temporary Immersion Bioreactor System (TIBS, Nanjing BioFunction Co. Ltd., China) and traditional test bottles. Dendrobine was unequivocally identified and characterised in D. nobile co-culture seedlings through UHPLC analysis and LC-MS qTOF analysis, supported by reference standards. The CGTB (control group) and EGTB (experimental group) 12-month-old D. nobile seedlings exhibited similar peak retention times at 7.6±0.1 minutes, with dendrobine identified as C16H25NO2 (molecular weight 264.195). The EGTB, co-cultured with Trichoderma longibrachiatum (MD33), displayed a 2.6-fold dendrobine increase (1804.23 ng/ml) compared to the CGTB (685.95 ng/ml). Furthermore, a bioanalytical approach was applied to investigate the monoculture of T. longibrachiatum MD33 with or without D. nobile seedlings in test bottles. The newly developed UHPLC-MS method allowed for dendrobine identification at a retention time of 7.6±0.1 minutes for control and 7.6±0.1 minutes for co-culture. Additionally, we explored TIBS to enhance dendrobine production. Co-culturing D. nobile seedlings with Trichoderma longibrachiatum (MD33) in the TIBS system led to a substantial 9.7-fold dendrobine increase (4415.77 ng/ml) compared to the control (454.01 ng/ml) after just 7 days. The comparative analysis of dendrobine concentration between EGTB and EGTIBS highlighted the remarkable potential of TIBS for optimizing dendrobine production. Future research may focus on scaling up the TIBS approach for commercial dendrobine production and investigating the underlying mechanisms for enhanced dendrobine biosynthesis in D. nobile. The structural elucidation of dendrobine was achieved through 1 H and 13 C NMR spectroscopy, revealing a complex array of proton environments and distinct carbon environments, providing essential insights for the comprehensive characterization of the compound. These findings hold promise for pharmaceutical and industrial applications of dendrobine and underline the role of endophytic fungi in enhancing secondary metabolite production in medicinal plants.